A new technique in the treatment of ureteroenteric anastomosis stricture: Repair of ureteroenteric anastomosis stricture with low lombotomy incision (retroperitoneal approach). Issue 6 (27th March 2021) - Kalemci, Serdar; Kizilay, Fuat; Simsir, Adnan
Abstract: Introduction and aim: Ureteroenteric anastomosis stricture (UEAS) is one of the complications of urinary diversion and may lead to serious consequences. In this study, we evaluated our UEAS revision technique outcomes performed with a low lombotomy incision in the lateral decubitus position. Materials and methods: Eleven patients who underwent surgical repair due to isolated right UEAS between January 2010 and June 2019 were included in the study. Anastomosis stricture was confirmed by ultrasonography, computed tomography or magnetic resonance urography techniques. Ultrasonography was used to detect hydronephrosis, which is a finding secondary to stricture. However, opaque urography imaging methods were used to confirm the definitive diagnosis of the stricture. Demographic and clinical data, preoperative and postoperative 3rd month serum creatinine, estimated glomerular filtration rate (eGFR) and dynamic renal scintigraphy data of patients were evaluated. Results: The mean operation time was 49.7 ± 9.3 minutes. No perioperative complications were observed. While the overall stricture rate was 11.4%, the isolated right‐sided stricture rate was 5.7%. Preoperative and postoperative serum creatinine values were similar. Preoperative eGFR value was 58.8 ± 12.9 mL/min/1.73 m 2 and postoperative value was 53.5 ± 11.5 mL/min/1.73 m 2 . T½ level decreased in postoperative period (22.3 ± 8.2 min vs 15.1 ± 4.3 min). Conclusions: Open revision of the UEAS with retroperitoneal approach provides lower morbidity rates and shorter hospitalisation time compared to other methods. The retroperitoneal approach is the main advantage of this technique and prevents morbidity caused by other techniques performed intraperitoneally and owing to it is an open technique, it can be easily applied in isolated right‐sided UEAS.